Wspólnoty intencjonalne jako przykład alternatywnego stylu życia - Ambroziński, Dariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Contemporary society is living in times of significant cultural changes, which is a consequence of technological development, globalization and social awareness. Distributed by mass media and producers consumerist lifestyle are no longer attractive to society. The result is an attempt to find an alternative. The gradual transformation of value systems often leads to choices that correspond to the concept of sustainable development. Society (community), cultural (spiritual) and ecological integration is realized by intentional communities. The most popular types of such housing community are ecovillages, and cohousings. Choosing the location and form of residence is a decision that affects the quality and style of life. Rebuilding your own lifestyle in line with the idea of sustainable development is a very difficult transition. The easiest way for society is submission to consumerism. This means that an in-depth analysis of own needs is required and often resignation of the desires, comforts and other amenities that are preferred over the common good. The importance of the problem is emphasized by the increasing demands of society that sustainable development is not a choice and a necessity leading to an improvement in the quality of life of present and future generations. The article attempts to present a new approach to sustainable development as an alternative to the consumerist lifestyle, in addition to identifying the types of intentional communities and assessing their development prospects
Keywords: lifestyle; intentional communities; consumerism; sustainable development; ecovillage